Development Of Halal Food Textbooks To Support Culinary Students' Achievement Of SDGs - Ratna Palupi Nurfatimah; Nugrahani Astuti; Hidayatun Muyasyaroh; Fitri Komala Sari; Hanif Naufal Ahmi (Universitas Negeri Padang, 2026)
The background of this research is the increasing demand for the Indonesian halal industry and the achievement of SDGs, as well as the limited comprehensive Halal Food teaching materials in universities. The aim of the research to develop and determine the feasibility of a textbook for undergraduate students of Culinary Arts Education, UNESA. The novelty of this research lies in the integration of three pillars: sharia aspects, certification regulations, and practical food technology (critical points) relevant to culinary vocations. The method used is the Research and Development (R&D) 4D model (Define, Design, Develop, Disseminate), the textbook was validated by 3 experts (material and media) and tested limited to 65 students as users. The results of quantitative descriptive analysis and data triangulation showed that the textbook was declared